Providing Cataract Surgeries at a Rural Primary Health Centre through Non-governmental Organisation Collaboration: An 8-year Experience - Shruti K Sharma; Vijay Sharma; Reena Yadav (Preventive Medicine: Research & Reviews, 2025)
The National Programme for Control of Blindness and Visual Impairment aims to reduce blindness and visual impairment in India. Despite these efforts, rural areas still have high numbers of cataract patients due to inadequate healthcare services. Leveraging non-governmental organisation (NGO) networks to provide rural eye care camps has been proposed to address these challenges. This article shares an 8-year collaboration with an NGO in rural Haryana, delivering cataract surgeries. Initially, surgeries were conducted in temporary locations; however, due to complications, they were shifted to hospitals, increasing travel difficulties. In 2016, collaboration with ICARE Eye Hospital began, involving screening camps and transporting patients for surgery. This reduced patient expenses and referral burdens, performing 1690 surgeries with high satisfaction. Authors recommend similar collaborations to achieve the national blindness reduction goal.